An In-Vitro Assessment of Anti-Tumor Activity of Some Plant Extract and Natural Products, Using Potato Discs Bioassay Technique - Yousif, Mohamed T.; Mohamed, Eiman Hassan; Mustafa, Salah Ahmed (Gezira Journal of Health Sciences; Vol 8 No 1 (2012), 2012)
Objectives: This study aimed to examine some plant extracts and natural products for anti-tumor activity. Methodology: Potato disc bioassay was used to estimate anti-tumor activity of some plant extracts and natural products. Five plant extracts and natural products recommended in a questionnaire filled by local botanists in addition to an introduced fermented food “Manda Koso” were used in this study. Study design: A questionnaire was designed and filled by 60 botanists looking for plant extracts and natural products having anti-cancer activity. In addition, computer surveys were conducted for gathering information on promising natural compounds act as anticancer agents. The potato disc bioassay was conducted using the Complete Randomized Design with three replicates. Each treatment in each replicate was represented by two Petri dishes contained five potato discs each. Petri dishes treated with sterilized water were used as control. Four separate experiments were carried out using TLC technique. Results & Discussion: Results showed highly significant differences among treatments with respect to total number of tumors and inhibition average percentage (%). The inhibition average percentage (IAP) for the different products ranged between 80.95-100% for the different products and equal zero for the control. It was 100% for Manda Kosa and bees honey followed by 90.23% for olive oil. Other treatments showed moderate anti-tumor effect of 80.95% IAP. Conclusions: Results concluded that Manda Koso, bees honey and olive oil have anti-tumor activity. Great association was found between anti-tumor activity obtained in this study and those published for anticancer activity of the promising material. الملخص: أجريت الدراسة بمعمل الاحياء الدقيقة بكلية الهندسة والتكنولوجيا بجامعة الجزيرة فى الفترة من 3 ابريل وحتى21 سبتمبر(2008) وذلك بغرض دراسة  مقدرة بعض المستخلصات النباتية على تثبيط  الاورام المستحثة باستخدام   سلالة محلية من  البكتيريا الزراعية  Agrobacterium tumefaceins تسمى SDB0012”" وذلك باستخدام تقنية قرص البطاطس وتقنية الفصل الكروماتوجرافى للتعرف على الجزيئات الفعالة للمستخلصات الطبيعية المستخدمة فى هذه الدراسة. اوضحت النتائج فروقات معنوية عالية ما بين المستخلصات المستخدمة في العدد الكلي للاورام  واحجامها.   اعطي  المستخلص اليابانى ماندا كوسو " Manda Koso" فعالية عالية على التثبيط الكلي للأورام المستحثة,  تليها عينة محلية لعسل النحل ثم زيت الزيتون ثم زيت الحبة السوداء (الكمون) ثم زيت الثوم  واقل نسبة رصدت في زيت الحلبة. أوصت الدراسة لاستخدام كل من ماندا كوسو, العسل و زيت الحبة السوداء كمثبطات نمو الاورام. اتضح من خلال هذه الدراسة فعالية استخدام تقنية اقراص البطاطس في تحديد مثبطات لنمو الاورام في كل من البطاطس والانسان وذلك من خلال تقارب النتائج بين هذا الاختبار في هذه التجربة و النتائج العالمية في هذه المستخلصات. هذا وقد اقترحت الدراسة إجراء استخدام تقنيات الفصل الكروماتوجرافى و كروماتوجرافيا الغاز GC و تقنية HPLC  بالاضافة لتقنية الهجرة الكهربية electrophoresis gel لفصل البروتينات .